2016
DOI: 10.21010/ajtcam.v14i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Stratification and Ga3 on Germination Ofarbutus Unedoseeds of Three Provenances

Abstract: Background: Arbutus unedo is a valuable Mediterranean shrub as an ornamental plant as well as fruit tree. Fresh fruits of A. unedo are a good source of antioxidants, of vitamins C, E and carotenoids and also are characterized by the high content of mineral elements. Materials and Methods: The effects of gibberellic acid (GA 3 ) and cold stratification (CS) on seed germination performance were investigated in A. unedo seeds collected from three provenances in the Northern part of Greece. Seeds of each provenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…In this study, the germination percentages of the half seeds and scarified seeds were significantly higher than those of the intact seeds (Figure 3), suggesting that E. ulmoides seeds likely have both PY and a shallow PD. These results were consistent with those of Yang et al [13,34]. According to the imbibition curve, from four hours of imbibition on, the water absorption of both the scarified seeds and the isolated embryos was significantly higher than the intact seeds (Figure 4).…”
Section: Determination Of the Dormancy Typesupporting
confidence: 91%
“…In this study, the germination percentages of the half seeds and scarified seeds were significantly higher than those of the intact seeds (Figure 3), suggesting that E. ulmoides seeds likely have both PY and a shallow PD. These results were consistent with those of Yang et al [13,34]. According to the imbibition curve, from four hours of imbibition on, the water absorption of both the scarified seeds and the isolated embryos was significantly higher than the intact seeds (Figure 4).…”
Section: Determination Of the Dormancy Typesupporting
confidence: 91%
“…According to Ricardo and Veloso (1987), about 90% and 50% of Arbutus unedo seeds treated only with 500 ppm GA3 germinated at 20°C and 25°C, respectively. In a study by Pipinis et al (2017), non-stratified seeds of three Arbutus unedo varieties that were not treated with GA3 solutions exhibited very low germination (0.83-7.50%). In the present study, like the above-mentioned studies, the highest germination percentage was observed with 500 ppm GA3 treatment, while the lowest germination was observed in the control group (without GA3 addition).…”
Section: Discussionmentioning
confidence: 98%
“…However, a major constraint to the sexual propagation of many species is the poor germination of their seeds. This is possibly due to low viability, although it is frequently due to seed dormancy (Mackay et al 2002, Pipinis et al 2017. Seed dormancy is a physiological condition in which the seeds cannot germinate even under the most suitable germination conditions that are in an environment with suitable temperatures, humidity and light conditions, or do not exhibit uniform germination.…”
Section: Introductionmentioning
confidence: 99%
“…Cold stratification treatment is an effective method for woody plants to alleviate seed dormancy [37], so it can be used to solve the physiological dormancy of Tilia seeds [38]. And GA 3 treatment can release seed dormancy early and shorten the duration of cold stratification [39]. Combined with magnetic field treatment, the germination time of most seeds was effectively advanced by 15 days.…”
Section: Discussionmentioning
confidence: 99%